How Bioinformatics Can Aid Biodiversity Description: The Case of a Probable New Species of Orthonychiurus (Collembola, Hexapoda) - Magalhaes, Maithe Gaspar Pontes; Melo, Marilia Alves Figueira; Queiroz, Gabriel Costa; Moreira, Aline dos Santos; Degrave, Wim; Parente, Thiago Estevam (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2022: Anais do XV Simpósio Brasileiro de Bioinformática, 2022)
The description of all living species is an ultimate goal of biology. Species description, however, is a time-consuming effort that requires specialized taxonomists in the vast array of existing taxa. With the current rate of habitat loss, it is plausible to assume more species are becoming extinct than what we could possibly describe. High-throughput sequencing together with the appropriate bioinformatic analyses is revolutionizing the knowledge regarding microbial biodiversity, but can also assist in the unraveling of the diversity of higher Eukaryotes. Here, we describe how transcriptome sequencing, de novo assemble, and BLAST analyses helped to identify the taxa of an unknown and abundant species sampled on the banks of a highly contaminated river in Rio de Janeiro, Brazil. This species is currently being described as a possible new species of Collembola (Hexapoda). In total, 4.589.437 paired-end 150 bp reads passed quality control and were used to assemble a de novo transcriptome, resulting in 44.013 transcripts with N50 of 1.338 bp. Of these assembled transcripts, 4.112 had a BLAST hit, with Folsomia candida (Collembola) being the most frequent species. Specimens of this sampled species were sent to a taxonomist specialized in Collembola for accurate taxonomic identification. The sampled specimens are being fully described and probably belong to a new species of Orthonychiurus (Hexapoda, Collembola, Onychiuridae).